Evaluating the Clinical Outcomes of Three Medication Regimens for Treating a Sample of Iraqi Persistent Asthmatic patients - Ali L. Jasim; Eman S. Saleh; Mustafa N. Abd Ali (College of Pharmacy University of Baghdad, 2020)
Abstract     Asthma is a complex disease defined by chronic airway inflammation and airflow limitation causing variable respiratory symptoms which include shortness of breath (SOB), wheezing, chest tightness and cough. Asthma guidelines advocate adding a second long acting bronchodilator to medium doses of inhaled corticosteroids (ICS) rather using high doses of ICS alone to control moderate to severe persistent asthma. The aim of this study was to evaluate the clinical outcomes of three medication regimens indicated for Iraqi patients suffering from persistent asthma.      This study was interventional randomized clinical study conducted on a sample of adult Iraqi asthmatic patients in Baghdad City. The study composed of three visits distributed over eight weeks; baseline visit followed by first follow up and second follow up visits after four and eight weeks respectively. The study enrolled 78 adult patients with moderate to severe persistent asthma as diagnosed by specialist physician according to patient history and baseline pulmonary function test (PFT) and allocated them randomly to three groups (each group included 26 patients) to receive equivalent medium doses of budesonide inhaler in addition to either formoterol inhaler, oral modified release aminophylline tablets or tiotropium inhaler (first, second and third group respectively). Sixty four patients completed this study. The mean ages of patients were above 35 years with slightly more male predominance.     The study groups developed significant increase of peak expiratory flow rate (PEFR) and forced vital capacity (FVC) values at the first follow up visit compared to baseline values (p<0.001). Thereafter, the first and third groups achieved significant higher values at the second follow up visit compared to first follow up visit (p<0.001), while second group produced no change. All the groups developed significant improvement of Mini asthma quality of life questionnaire (MiniAQLQ) scores and percentage of symptom free days (SFD) at first follow up visit and continued further significant improvement at the second follow up visit (p<0.001). Generally, between groups comparison according to extent of change of study parameters revealed that third group produced the greatest improvement over the entire study period followed by the first group, whereas the second group was associated with the least extent of improvement.     This study concluded that all groups caused significant improvement in study parameters compared to baseline values and also concluded that the third group of inhaled [tiotropium/budesonide] was associated with the highest extent of improvement followed by first group, while the second group was the least.